Virus-like particles and cytoplasmic inclusions associated with diseased Dioscorea rotundata poir from Nigeria - Mohamed, N.A.; Terry, Eugene R. (1979)
Dioscorea rotundata plants from Nigeria showing green vein banding and shoe-string symptoms were found to be infected with a flexuous rod-shaped virus, about 805nm long. Infected leaves contained masses of filamentous virus-like particles and cytoplasmic inclusions usually associated with infection by potyviruses; however, no true pinwheels were present. This virus may differ from that infecting yams in the West Indies on the basis of the different inclusions found in infected tissues.